TISCs report 2023 : cultivating expertise to empower local innovators. (WIPO publication ;, 2024)
"This annual report of Technology and Innovation Support Centers (TISCs) highlights the main developments and milestones in 2023, with a focus on how TISCs in 93 countries and technology transfer structures continued to expand their services to meet the needs of local innovators, and how WIPO supports them with new resources."--